2000
DOI: 10.1148/radiology.214.1.r00ja13143
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Ethanol Injection of Large Autonomous Hyperfunctioning Thyroid Nodules

Abstract: PEI is an effective and safe technique for the treatment of large hyperfunctioning thyroid nodules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
19
0
4

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 13 publications
4
19
0
4
Order By: Relevance
“…They all have some advantages on surgery: no hiatrogenic hypothyroidism, no scar formation, lesser costs. Adverse events are comparable: the most common major adverse effect, recurrent laryngeal nerve palsy, is 11.8% (9.8% transient, 2% permanent) in surgery (18) and 0-8% (only transient) in RFA and LA (6)(7)(8)17,(19)(20)(21)(22)(23). PEI has revealed to be useful for cystic nodules: it can be used with fine needles (21G), and is quite inexpensive and shows good results (53-80% reduction in volume) (24).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They all have some advantages on surgery: no hiatrogenic hypothyroidism, no scar formation, lesser costs. Adverse events are comparable: the most common major adverse effect, recurrent laryngeal nerve palsy, is 11.8% (9.8% transient, 2% permanent) in surgery (18) and 0-8% (only transient) in RFA and LA (6)(7)(8)17,(19)(20)(21)(22)(23). PEI has revealed to be useful for cystic nodules: it can be used with fine needles (21G), and is quite inexpensive and shows good results (53-80% reduction in volume) (24).…”
Section: Discussionmentioning
confidence: 99%
“…Surgery has in fact some limitations, like a 2-10% complication rate, hiatrogenic hypothyroidism, hospitalization, general anesthesia and scar formation (5). In the last years, non surgical minimally invasive techniques have been developed to treat this pathology, starting from percutaneous ethanol injection (PEI), to laser ablation (LA) and radiofrequency ablation (RFA) (6)(7)(8). Most recently, microwave ablation (MWA) has been proposed to treat thyroid nodules, taking experience from its use in other organs like liver, kidney and lung in particular (9).…”
Section: Introductionmentioning
confidence: 99%
“…Studies that have examined the use of EA to treat benign solid thyroid nodules have shown varying levels of success, depending on nodule size, the volume of ethanol instilled, and the presence of nodule toxicity. [10][11][12][13][14] However, the author of this study has recently found that EA may be a viable alternative to RFA or surgery for the treatment of these nodules. 15 In addition, to the best of my knowledge, no study has previously examined the feasibility of using EA to remove any peripherally located solid components remaining after treatment of benign solid thyroid nodules with RFA.…”
mentioning
confidence: 88%
“…The conservative approach is not helpful for the uncomfortable feeling of a lump in the throat or cosmetic concerns. Therefore, nonsurgical, minimally invasive modalities, such as ethanol injection, laser ablation, and radiofrequency ablation (RFA), have been attempted, yielding good results (2,3,4,5).…”
Section: Introductionmentioning
confidence: 99%